Not in the mood? Men under- (not over-) perceive their partner's sexual desire in established intimate relationships. [article]. - Muise, Amy.
Men's sexual overperception bias-where men tend to perceive greater sexual interest in women's behavior than actually exists-is a well-documented finding in previous research. All of the existing research, however, has tested this effect in the context of initial encounters or for fictitious or unknown targets. No research currently exists on how people perceive their romantic partner's sexual desire in the context of ongoing, intimate relationships. In 3 dyadic studies, we provide evidence that men in established romantic relationships err in the direction of the opposite bias and underperceive their romantic partner's sexual desire. We also demonstrate that this underperception bias is functional (particularly for men) in that it is associated with their partner feeling more satisfied and committed to the relationship. In addition, people are particularly likely to underperceive their partner's desire on days when they are motivated to avoid sexual rejection, and men's underperception bias is, in part, accounted for by men's higher general levels of sexual desire than women. The current studies extend previous findings on sexual perceptual biases and demonstrate the important role of context in men's judgments of a partner's sexual interest. -- (from the authors)
Keywords: Stanton, Sarah C. E; Evolutionary theory; Men's sexual perception bias; Romantic relationships; Sexual rejection; Sexual desire